A Survey on Conformance Checking of Event Logs and Process Models in Business Organization - G., Pavithra; J. , Ranjith; B. , Adithya (International Journal of Psychosocial Rehabilitation, 2020)
Process mining is a developing technology. It is used in the field of administration. It deals with Process Discovery (PD), Conformance Checking (CC), and Process Enhancement (PE) based on logs and models. In conformance checking (CC), it takes the current process model as input and compares it with the event logs of the actual execution of the business process and the resulting model by capturing the predictable performance of the given process. CC can be used to check whether the process model as recorded in the event log conforms to the process model and vice versa. It is challenging to determine the optimal alignment for each of the event logs and the process model because of their similarity with the event log. The main objective of this study is to provide an overall knowledge about the CC in context with the event logs and process model. A series of metrics based on prior work are introduced to perform conformance checking. The proposed metrics include fitness, precision, generalization, and simplicity.